Analisis Akuntabilitas Pengelolaan Alokasi Dana Desa Dan Pendapatan Desa Di Desa Sigam Kecamatan Gelumbang Kabupaten Muara Enim Tahun 2017-2019 - Mahdi Hendrich; Sri Sutandi; Irsan; Roy Saleh; Asti Arisandi (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2021)
The purpose of this study was to answer the question of how to analyze the accountability of village fund allocations in Sigam Village, Gelumbang District, Muara Enim Regency. The result of this study is that the accountability for village fund allocations, both technically and administratively, has been running well according to applicable regulations with evidence of accountability in a transparent and accountable manner. But there are obstacles faced by village officials, namely by using the application system and not accompanied by sufficient training so that accountability reports using the application system complicate village financial tasks. Meanwhile, the management of village revenue budgets in general has been well managed. The obstacle faced by village officials is that it is still difficult to record the preparation of village financial books because of changing policies so that they still need assistance from local government officials in order to adjust the changes in regulations every year that runs. The suggestion submitted by the researcher for Sigam Village is for the Sigam Village Government to continuously improve by always following the latest laws and regulations, so that the village government can manage the budget well and maintain the principles of accountability and transparency.